HUBUNGAN PENGETAHUAN IBU BERSALIN TENTANG NYERI KALA I FASE AKTIF DENGAN PENGENDALIAN NYERI DI PUSKESMAS BINJAI ESTATE TAHUN 2025 - NINGSIH SAFARI, FIFI RIA; Sinaga , Eliza Bestari; Pane, Efi Irwansyah; Rezeki, R. Sri; Legawati, Sri (Jurnal Kesehatan Ilmiah Aufa Royhan, 2026)
Labor pain is a physiological experience that is almost always experienced by mothers giving birth, especially during the first active phase. Uncontrolled pain intensity can cause anxiety and disrupt the mother's comfort during labor. One factor that influences the mother's ability to control pain is the level of knowledge. This study aims to determine the relationship between mothers' knowledge about the first active phase of labor pain and pain control at the Binjai Estate Community Health Center, Binjai City. This study used a quantitative design with a correlational analytical approach and a cross-sectional method. The population in this study were all mothers giving birth in the first active phase at the Binjai Estate Community Health Center, Binjai City in 2025, totaling 50 people, with a total sampling technique. Data collection was carried out using a structured questionnaire, then analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that most respondents had a low level of knowledge and uncontrolled pain control. Statistical tests showed a significant relationship between mothers' knowledge and pain control at the first active phase with a p value = 0.015 (p < 0.05). The conclusion of this study is that maternal knowledge during labor is significantly related to pain management skills during the active phase of the first stage of labor. Therefore, increased antenatal education and counseling regarding labor pain and how to manage it are necessary to optimize maternal comfort during labor.